The Relationship Between Workload And The Performance Of Medical Record Officers: A Case Study Of Four Hospitals In The City Of Pekanbaru - Sari, Tri Purnama; binti Ahmad Shakir, Khairunnisak; Binti Bahari, Asnani (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Medical records play a crucial role in supporting the quality of healthcare services, yet the performance of medical record officers is often constrained by high workloads. This study aimed to analyze the relationship between workload and performance of medical record officers using a quantitative cross-sectional design involving 100respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed